Treatment Failure in Scabies: Assessment of Risk Factors in a Multicenter Cross-Sectional Study - Erdem, Yasemin; Polat Ekinci, Algun; Ergun, Mucahit; Bulat, Ceylan; Kırker, Artun; Turgut, Hamit Dogus; Cesur, Afra; Altunay, Ilknur Kıvanc; Topkarci, Zeynep (Dermatology Practical & Conceptual, 2025)
Introduction: Recent reports of increased prevalence and treatment failure in scabies have raised concerns worldwide. Drug efficacy as well as adherence to treatment are important in treatment failure, and data on the latter are limited. Objective: We aimed to determine the factors associated with treatment failure in scabies. Methods: This prospective, multicenter observational study was conducted in three centers, enrolling 230 patients diagnosed with scabies. Treatment outcomes were assessed one month after treatment initiation. Patients completed a questionnaire evaluating factors potentially affecting treatment outcomes. Demographic and clinical characteristics and adherence to treatment recommendations were compared in two groups: successful treatment and treatment failure. Results: The study included 125 males and 105 females, with a mean age of 24.6 ±17.6 years. Treatment failure was found in 58 patients (25.2%). No demographic parameter or medication was associated with treatment failure. Three independent risk factors for treatment failure (multivariate regression analysis) were lack of application of topical medication to the whole body, (odds ration (OR): 14.33; 95% confidence interval (CI): 2.9–71.4), lack of reapplication after washing hands (OR: 3.5; 95% CI: 1.5–8.0), and not reading of the information form (OR: 13.7; 95% CI: 1.3–80.6). Conclusion: Treatment failure in scabies is quite common. Incorrect or incomplete application of topical treatment and lack of hygiene measures are the main factors leading to treatment failure. Providing a written information sheet with step-by-step treatment recommendations may contribute to treatment success.